2001
DOI: 10.1046/j.1432-1327.2001.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretory ribonucleases in the primitive ruminant chevrotain (Tragulus javanicus)

Abstract: Phylogenetic analyses of secretory ribonucleases or RNases 1 have shown that gene duplication events, giving rise to three paralogous genes (pancreatic, seminal and brain RNase), occurred during the evolution of ancestral ruminants. A higher number of paralogous sequences are present in chevrotain (Tragulus javanicus), the earliest diverged taxon within the ruminants. Two pancreatic RNase sequences were identified, one encoding the pancreatic enzyme, the other encoding a pseudogene. The identity of the pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…, leaf-eating monkeys), in which two independent RNASE1 gene duplication events have been found in Asian colobine and African colobine subfamilies12131415. In comparison, the RNASE1 gene duplication pattern in the ruminant artiodactyls is different, which has been reported to arise through ancient gene duplication events in the common ancestor of all ruminants627, rather than independent duplications. Furthermore, several other lines of evidence support the independent diversifications of RNASE1 genes in four Musteloidea families discovered here: (1) the alternative tree topology supporting a single-gene duplication event prior to the divergence of the four families of Musteloidea was significantly worse than our presented tree (P < 0.05) under the Kishino-Hasegawa test28 and the Shimodaira-Hasegawa test29; and (2) no signals of gene conversion events, which can lead to spurious independent duplications by homogenizing sequences within species, were found using GENECOVN software30, suggesting that the observed family-specific clusters were not the results of concerted evolution via gene conversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, leaf-eating monkeys), in which two independent RNASE1 gene duplication events have been found in Asian colobine and African colobine subfamilies12131415. In comparison, the RNASE1 gene duplication pattern in the ruminant artiodactyls is different, which has been reported to arise through ancient gene duplication events in the common ancestor of all ruminants627, rather than independent duplications. Furthermore, several other lines of evidence support the independent diversifications of RNASE1 genes in four Musteloidea families discovered here: (1) the alternative tree topology supporting a single-gene duplication event prior to the divergence of the four families of Musteloidea was significantly worse than our presented tree (P < 0.05) under the Kishino-Hasegawa test28 and the Shimodaira-Hasegawa test29; and (2) no signals of gene conversion events, which can lead to spurious independent duplications by homogenizing sequences within species, were found using GENECOVN software30, suggesting that the observed family-specific clusters were not the results of concerted evolution via gene conversion.…”
Section: Discussionmentioning
confidence: 99%
“…The RNASE1 gene has been thoroughly investigated in many mammalian herbivores having multicompartmentalized stomachs, like ruminants ( e.g. ox, sheep and camel)1234567, and species with ruminant-like or cecal digestions ( e.g. leaf-eating colobines and elephants)89101112131415.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNASE1 gene duplication has been found in many mammals with multi-compartmentalized stomachs, such as ruminants (e.g., cows, sheep, and camels) (Kleineidam et al 1999; Breukelman et al 2001), and species with ruminant-like or cecal digestions (e.g., leaf-eating colobines and elephants) (Zhang et al 2002; Yu et al 2010; Goo and Cho 2013; Zhou et al 2014). Gene duplication of RNASE1 is believed to be correlated with the plant-feeding adaptation of foregut-fermenting herbivores (Liu et al 2014), and ruminant artiodactyls have considerably higher concentrations of pancreatic RNASE1 than other mammals (Zhang 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed at high levels in the pancreas of ruminants with ruminant digestion and also a number of species with ruminant-like or cecal digestion to degrade large amounts of RNA released by symbiotic bacteria from herbivorous stomach or cecum in order to gain nutrients [17][18][19][20]. While most mammals have only one RNASE1 gene, ruminants and ruminant-like animals were found to have multiple RNASE1 genes resulting from gene duplications, including ox, sheep, camel, rat, guinea pig and elephant [21][22][23][24][25][26][27]. Using both molecular analyses and functional assays, Zhang et al [28][29][30] have revealed that the duplicated RNASE1 genes in two colobines, Asian Pygathrix nemaeus and African Colobus guereza, evolved rapidly under positive selection for enhanced digestive efficiencies, as an adaptive response to the increased demands for the enzyme for digesting bacterial RNA.…”
mentioning
confidence: 99%